2017
DOI: 10.1136/jim-2016-000224
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Validity of the Acs-Nsqip Risk Calculator in Plastic Surgery: Lack of Input Specificity, Outcome Variability and Imprecise Risk Calculations

Abstract: American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) created the Surgical Risk Calculator, to allow physicians to offer patients a risk-adjusted 30-day surgical outcome prediction. This tool has not yet been validated in plastic surgery. A retrospective analysis of all plastic surgery-specific complications from a quality assurance database from September 2013 through July 2015 was performed. Patient preoperative risk factors were entered into the ACS Surgical Risk Calculator,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Additional points are awarded for antibiotic treatment, drainage of pus under local anesthesia, debridement of the wound under general anesthesia, isolation of bacteria, and stay as inpatient prolonged over 14 days. Scores are grouped into 4 categories: satisfactory healing (0-10), disturbance of healing (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), minor SSI (21-30), moderate SSI (31-40), and severe SSI (>40). The original ASEPSIS score is meant to evaluate the surgical site for infections from day 5 to 7 postoperatively.…”
Section: Asepsis Scorementioning
confidence: 99%
“…Additional points are awarded for antibiotic treatment, drainage of pus under local anesthesia, debridement of the wound under general anesthesia, isolation of bacteria, and stay as inpatient prolonged over 14 days. Scores are grouped into 4 categories: satisfactory healing (0-10), disturbance of healing (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), minor SSI (21-30), moderate SSI (31-40), and severe SSI (>40). The original ASEPSIS score is meant to evaluate the surgical site for infections from day 5 to 7 postoperatively.…”
Section: Asepsis Scorementioning
confidence: 99%
“…13 Although this databasehas been applied across surgical subspecialties, there are concerns over its 30-day postoperative window and the possibility of it underrepresenting the entirety of complications a patient can experience in the postoperative period. 14,15 We recently published results on infectious readmission rates in patients who underwent implant-based breast reconstruction. We found that 50.7% of infectious readmissions occurred between a 31-and 90-day postoperative period, leading us to conclude that traditional 30-day readmission rates were inadequate to track that specific patient population.…”
mentioning
confidence: 99%
“…It has been argued that the NSQIP poorly estimates complication rates by missing important outcomes including post-operative readmission, infections, and hematomas. 8,62,118 This was reflected in some studies included in this review that directly analyzed the validity of NSQIP as an outcome tool for plastic surgery. This may be attributed to the fact that the NSQIP was created from a disease-specific colorectal risk calculator.…”
Section: Critiquesmentioning
confidence: 99%